Business Unit Management Model After the Implementation of the Regulation of The Minister of Religious Affair (PMA) No 19 of Year 2017 - Erwin Erwin; Misneli Misneli (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Purpose: The Paper is to to find out changing management model of State Islamic University (UIN) business units in Indonesia after the change of Institutional status from State Islamic Institute (IAIN) to State Islamic University (UIN) in accordance with PMA No.19 Year 2017.Design/Method/Approach: This study uses a descriptive analysis. It The research employed a mixed method between qualitative research methods and quantitative methods. Quantitative method was used because this research also distributed questionnaires related to environmental responses to the existence of business development units while the qualitative method was used to describe the condition of the Business Development Unit in each university using Research and Development model.Findings: The results of this paper are designed management from whole of problems found in each UIN after the status converted.Originality/Values: The main contribution of this study concern on management model of UIN business in Indonesia after the change of Institutional status from state Islamic Institute to state Islamic university in accordance with PMA no 19 2017.